Proliferative flexor tenosynovitis in the index finger of a 10-year-old baseball player gloved hand: A case report. (April 2022) - Tajika, Tsuyoshi; Saito, Kenichi; Tomomatsu, Yusuke; Kuboi, Takuro; Hatori, Yuhei; Hirato, Junko; Yanagawa, Takashi; Chikuda, Hirotaka
Flexor tenosynovitis is rare in young children. This case report describes that of a 10-year-old boy with diffuse swelling of the left index finger, pain when catching a ball, and progressive inability for full flexing of the finger 2 months after starting baseball play. Magnetic resonance imaging showed a defined lesion with iso-signal intensity to muscle on T1-weighted imaging, and with high signal intensity to muscle on T2-weighted imaging. It was enhanced in T1-weighted fat suppression imaging with gadolinium enhancement. Surgical excision relieved the symptom. Histopathological findings mainly indicated proliferation of synoviocytes and plasma cell and lymphocyte infiltration. We speculated that the physical impact of the ball on the left index finger of his gloved hand during catching activated some immunological mechanism and thereby caused nonspecific tenosynovitis in this young baseball player. Awareness of this pathophysiology might raise confidence in proper diagnosis for assessing the swelling of fingers in young baseball players.